Nutrisi Seimbang dan Pengolahan Pangan Lokal Untuk Anak - Solehudin, Solehudin; Irma Herliana; Yeni Koto; Nur Eni Lestari; Lannasari Lannasari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Local food is often fresher and has a higher nutritional content. Local foods have usually adapted to local soil and climate conditions, which makes them easier to grow and process by local people. Local food consumption is often in harmony with the culture and traditions of local communities, which usually have recipes and processing methods that support nutritional balance. The purpose of writing the article is to understand the growth and development of babies and toddlers to grow into healthy children by providing a balanced diet. Community service activities are carried out by professional nurse lecturers who teach community and family nursing courses. Community service together with professional nursing students who are practicing community and family nursing. The counseling and simulation will be held on Friday 12 June 2024 at 09.00 – 12.00 WIB in the Madrasah Marga Jaya room RT 02 RW 05 Kertamaya Village, Bogor City. Local plant ingredients are very useful for maintaining nutritional balance in babies and toddlers. Increasing public interest in using local food ingredients as a source of nutrition requires a multifaceted and integrated approach.